An Integrated Systems Architecture to Provide Maritime Domain Protection - McCarthy,C; Wyllie,R; Vaidyanathan,R; Paulo,EP (The Journal of Defense Modeling and Simulation: Applications, Methodology, Technology, 2006)
The focus of this research is to address the criticality and vulnerability of commercial shipping in the Straits of Mallacca by designing and evaluating competing systems architectures that could provide sufficient maritime domain protection. The category of primary concern was the introduction of a weapon of mass destruction (WMD) in a cargo container. The Maritime Domain Protection (MDP) physical architecture alternatives combined five separate systems: 1) a land-based cargo inspection system, 2) a sensor system, 3) a C3I (command and control, communications, and intelligence) system, 4) a force response system, and 5) a sea-based cargo inspection system. Individual models for each system were developed and combined into an overarching integrated architecture model to evaluate overall performance. Study results based on current technology showed that while solutions were found to effectively reduce risk in the WMD threat scenario, effective suppression came at great expense and included the participation of commercial shipping companies. A range of alternative cost-effective solutions were also found, but with limited performance. Future work involves using the developed architecture as a test bed for evaluating the overall impact and effectiveness of new technologies and research (such as “smart containers”) on MDP and homeland security.